2000
DOI: 10.3109/10428190009148404
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by 2-Chloro-2'deoxyadenosine (2-CdA) Alone and In Combination with other Cytotoxic Drugs: Synergistic Effects on Normal and Neoplastic Lymphocytes by Addition of Doxorubicin and Mitoxantrone

Abstract: 2-CdA is active as a single agent in the treatment of low-grade lymphomas. We analyzed the induction of apoptosis by 2-CdA alone (n=5) and in combination with other drugs in peripheral lymphocytes from 25 patients with leukemic low-grade lymphomas and from 25 healthy volunteers. 2-CdA was tested in 4 escalating concentrations (0.05 microg/ml to 0.4 microg/ml). Linear regressions showed a dose dependent apoptosis rate of 0.29 x microg 2-CdA/ml + 0.11 (r2=0.88, p=0.006) in normal cells and 0.41 x microg 2-CdA/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…However, currently, PNA administration has become a useful tool in treating young persons and even children. Indeed, positive effects of cladribine in the treatment of chronic lymphocytic leukemia have been described (Chow et al 2000), as its efficacy in treating NHL [Chow et al 2000], mantle cell lymphoma (Inwards et al 2008), AML (Wierzbowska et al 2008), myelodysplastic syndromes (Laurencet et al 1997), chronic myeloid leukemia (Martinelli et al 1996), Waldenström macroglobulinemia (Rourke et al 2010), histiocytosis, also in children (Mottl et al 2006), astrocytomas (Ceruti et al 2000, Ceruti et al 2003), multiple sclerosis (Hartung 2009; Leist and Weissert 2011; Vosoughi and Freedman 2010), mast cell disease (Aichberger et al 2008), psoriasis, including psoriatic arthritis (Eibschutz et al 1995), systemic lupus erythematosus (Bernknopf et al 2011), angioedema, and anaphylaxis (Dutta et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…However, currently, PNA administration has become a useful tool in treating young persons and even children. Indeed, positive effects of cladribine in the treatment of chronic lymphocytic leukemia have been described (Chow et al 2000), as its efficacy in treating NHL [Chow et al 2000], mantle cell lymphoma (Inwards et al 2008), AML (Wierzbowska et al 2008), myelodysplastic syndromes (Laurencet et al 1997), chronic myeloid leukemia (Martinelli et al 1996), Waldenström macroglobulinemia (Rourke et al 2010), histiocytosis, also in children (Mottl et al 2006), astrocytomas (Ceruti et al 2000, Ceruti et al 2003), multiple sclerosis (Hartung 2009; Leist and Weissert 2011; Vosoughi and Freedman 2010), mast cell disease (Aichberger et al 2008), psoriasis, including psoriatic arthritis (Eibschutz et al 1995), systemic lupus erythematosus (Bernknopf et al 2011), angioedema, and anaphylaxis (Dutta et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Among the proposed mechanisms are a direct interference with DNA and RNA biosynthesis, DNA repair, induction of apoptosis in leukemic cells, cell cycle control, or signal transduction pathways (8,10,11). A number of studies have investigated the use of cladribine or fludarabine in monotherapy or in combinations with different drugs such as alkylating agents, glucocorticoids, and anthracyclines (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…91,92 Recent clinical observations have demonstrated that the combinations of FAMP or 2-CdA with mitoxantrone, doxorubicin or epirubicin are effective in CLL. 56,[93][94][95][96] Combined treatment with NA, mitoxantrone and CY has been undertaken both in previously treated and untreated patients with B-CLL.…”
Section: Nucleoside Analogues In Combination With Other Agentsmentioning
confidence: 99%